An introduction to language and linguistics - Holmes, Janet (Cambridge, UK : Pearson Education Limited, 2001)
This text explains basic sociolinguistics concepts through a wide range of examples and by drawing on classic approaches to the subject as well as from the most recent research. It examines how and why languages change within society.
Includes bibliographical references and index.
Keywords: Sociolinguistics